2012
DOI: 10.1111/j.1759-7714.2011.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and survival of lung cancer in the idiopathic pulmonary fibrosis

Abstract: Background: The aim of this study was to evaluate the prevalence, risk factors, and survival of lung cancer in patients with idiopathic pulmonary fibrosis (IPF). Methods: IPF with lung cancer from tertiary hospitals consisted of 1685 patients who had been diagnosed between 2003 and 2007. We reviewed their medical records retrospectively to evaluate the prevalence, risk factors and prognosis of lung cancer in IPF patients. Results: Among all patients with IPF, 114 cases (6.8%) had lung cancer with IPF. The inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
42
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 16 publications
(40 reference statements)
8
42
0
2
Order By: Relevance
“…The prevalence of lung cancer among IPF patients was reported in 15 studies [26,28,34,48,[82][83][84][85][86][87][88][89][90][91][92] (online supplementary table S4 and figure 5) and was typically lower than the prevalence of other respiratory comorbidities of interest. Analyses of insurance claims and electronic medical records databases from the USA and the UK estimated the prevalence of lung cancer to be 3-4% [26,82,83].…”
Section: Lung Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…The prevalence of lung cancer among IPF patients was reported in 15 studies [26,28,34,48,[82][83][84][85][86][87][88][89][90][91][92] (online supplementary table S4 and figure 5) and was typically lower than the prevalence of other respiratory comorbidities of interest. Analyses of insurance claims and electronic medical records databases from the USA and the UK estimated the prevalence of lung cancer to be 3-4% [26,82,83].…”
Section: Lung Cancermentioning
confidence: 99%
“…30-day, 90-day, in-hospital) tended to be low (0 deaths [95,96], 4% [96,97], 5% [98], 7% [97], 8% [98,99], 12% [93,98]), although a small database review from China reported a post-operative mortality rate of 33.3% (two of six patients) [84]. Median survival from IPF diagnosis was between 7 (95% CI 2.51-11.49) and 26.9 months (95% CI 14.67-39.05) [84,89]. Two studies reported no significant difference in median survival between IPF-alone and IPF patients with lung cancer [84,85].…”
Section: Lung Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were reported basing on a South Korean study sample, where lung cancer prevalence in IPF patients was 6.8%. Among 89 IPF subjects, a simultaneous diagnosis of lung cancer and IPF was established in 78.1% of cases [33].…”
Section: Epidemiologymentioning
confidence: 99%